Pengaruh Gaya Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Kinerja Karyawan pada Hotel The Jayakarta Suites Komodo Flores - Felisima Ica; Kornelius Yoseph Paga Meka; Yohana Cintami Lery; Hersanius Kurnia Peong (JURNAL AKADEMISI VOKASI, 2024)
Labuan Bajo is an area prioritized as a tourist destination by the current government. This has an impact on increasing competition in the hotel business in Labuan Bajo. The Jayakarta Suites Komodo Flores Hotel is one of the companies providing lodging services that is well known in Labuan Bajo. This research aims to analyze the influence of transformational leadership style and work motivation on employee performance at The Jayakarta Suites Komodo Flores hotel. The population in this study was 54 employees and was used as the research sample. The analysis technique used is a multiple linear regression model. The research results show that transformational leadership style and work motivation partially have a significant effect on employee performance. Simultaneously, transformational leadership style and work motivation have a significant effect on employee performance.